Patient preferences regarding pharmacologic venous thromboembolism prophylaxis. Issue 2 (22nd November 2014) - Wong, Adrian; Kraus, Peggy S.; Lau, Brandyn D.; Streiff, Michael B.; Haut, Elliott R.; Hobson, Deborah B.; Shermock, Kenneth M.
<x xml:space="preserve">Abstract</x> BACKGROUND The 2012 American College of Chest Physicians venous thromboembolism prevention guidelines emphasized the importance of considering patient preferences when ordering venous thromboembolism prophylaxis. OBJECTIVE Determine patient preferences regarding pharmacologic venous thromboembolism prophylaxis. DESIGN Single‐center, mixed‐methods survey. SETTING Academic medical center. PATIENTS Consecutive hospitalized patients on surgical and medical units. MEASUREMENTS Patients were asked about their preferences regarding the route of administration for pharmacologic venous thromboembolism prophylaxis and the rationale for their preference. Qualitative analyses of themes were determined from patient rationale. RESULTS Of the 227 patients, a majority (60.4%) preferred an oral medication, if equally effective to subcutaneous options. Dislike of needles (30.0%) and pain from injection (27.7%) were identified as rationales for their preference. Patients favoring subcutaneous administration (27.5%) identified a presumed faster onset of action (40.3%) as the primary reason for their preference. Patients with a preference for subcutaneous injections were less likely to refuse prophylaxis than patients who preferred an oral route of administration (37.5% vs 51.3%, P < 0.0001). LIMITATION Only medical and surgical patients participated. CONCLUSION In a sample of consecutive medical and surgical patients, a majority preferred an oral route of administration for prophylaxis. Patients preferring subcutaneous injections were less likely to refuse doses of ordered pharmacologic prophylaxis. These results indicate use of an oral agent for venous thromboembolism prophylaxis may improve adherence and that integrating patient preferences into care may increase delivery of effective prophylaxis and reduce the incidence of venous thromboembolism. Journal of Hospital Medicine 2015;10:108–111. © 2014 Society of Hospital Medicine